"One of these things is not like the others": The associations between dark triad personality traits, work attitudes, and work-related motivation. (April 2023) - Szabó, Zsolt Péter; Diller, Sandra J.; Czibor, Andrea; Restás, Péter; Jonas, Eva; Frey, Dieter
Abstract: Our research investigated whether the dark triad personality traits relate to work attitude including work-related motivation, organizational identification, organizational commitment, and job satisfaction. We hypothesized that subclinical narcissism is associated positively, while subclinical psychopathy is associated negatively with work attitude. We also investigated the relationships between Machiavellianism and work attitude but did not formulate any hypothesis because of the mixed previous findings. Two studies ( N Total  = 688) assessed these predictions. Importantly, in Study 2 we obtained both self-report and observer-report measures of dark triad traits and achievement motivation. Results supported our predictions. The findings suggest that each dark triad trait has a distinct relationship with work outcomes. Furthermore, the participants' self- and other-rated dark triad personality traits only correlated weakly. Implications of these findings are discussed. Highlights: Each dark triad trait relates differently to work attitude and work motivation. Narcissism is consistently a positive predictor of work attitude and motivation. Psychopathy relates negatively to job satisfaction and organizational commitment. Machiavellianism is related to materialistic motivation and achievement motivation. The self-reported and observer-reported dark triad traits are only weakly correlated.